The Impact of Migration on Population Ageing in Asia 1990-2020: A Decomposition Analysis Using Prospective Age - Dörflinger, Markus (Comparative population studies, 2025)
Population ageing has become a global trend, which unfolds at different speeds across world regions and countries. In Asia, there are countries with rapidly ageing populations and those that continue to maintain a younger age structure. One potential driver of this difference is international migration. In this study, I assess the impact of migration on population ageing in Asian countries over the period 1990-2020. To do so, I propose a refined decomposition method, applying a prospective view on population ageing that accounts for variation in life expectancy. Using data from the United Nations World Population Prospects 2022, changes in the prospective old-age dependency ratio in 51 countries are decomposed into the effects of cohort turnover, deaths, changes in life expectancy and net migration. The results reveal that cohort turnover and deaths have had the largest impact on changes in the prospective old-age dependency ratio over the last three decades, whereas the impact of international migration and changes in life expectancy was smaller in all countries. However, in countries with either highly negative or highly positive net migration, the effect of migration on the age structure is substantial. As migration largely occurs at younger ages, high immigration has decelerated or even halted the process of population ageing in countries such as Bahrain, Macao, Oman and Singapore. The opposite effect is observed in emigration countries such as Armenia, Georgia and Timor-Leste. Hence, the large differences in the current level of population ageing across Asian countries can at least partly be attributed to international migration in the last decades.